Living Together
VI, 230 p.
Keywords: The papers in this book provide international perspectives on the possibilities for and challenges facing intercultural dialogue in education. These challenges are many in a world characterized by the tensions and demands of both global and local issues as well as regional conflicts. This is especially so as post-conflict deliberations are complicated by the cultural, religious and linguistic diversity within both small and large states. The authors here analyze the interplay between intercultural dialogue, education and the state, and reveal how educational experiences are able either to exacerbate problems, or mitigate them by promoting an intercultural dialogue of reconciliation as well as recognition of shared values. The mere act of collaborating in educational endeavor can itself have a positive impact. The outcomes of attempts at intercultural understanding are examined by educational researchers from high- and low-income countries, from the east and the west, and from both northern and southern hemispheres. The authors demonstrate the value of disciplined comparison of differing education societies, and detail the international research aimed at augmenting cross- and intercultural understanding. This exciting and wide-ranging volume has been facilitated by the World Council of Comparative Education Societies and affords compelling visions of the ways in which education can be a force for good in our highly diverse societies by fostering intercultural dialogue.